Toll‐like receptor variation in the bottlenecked population of the endangered Seychelles warbler. (13th October 2016) - Gilroy, D. L.; van Oosterhout, C.; Komdeur, J.; Richardson, D. S.
Abstract: In small populations, drift results in a loss of genetic variation, which reduces adaptive evolutionary potential. Furthermore, the probability of consanguineous mating increases which may result in inbreeding depression. Under certain circumstances, balancing selection can counteract drift and maintain variation at key loci. Identifying such loci is important from a conservation perspective and may provide insight into how different evolutionary forces interact in small populations. Toll‐like receptor (TLR) genes play a pivotal role in vertebrate innate immune defence by recognizing invading pathogens. We characterize TLR variation in the Seychelles warbler (SW) Acrocephalus sechellensis, an endangered passerine that recently suffered a population bottleneck. Five of seven TLR loci were polymorphic, with one locus ( TLR15 ) containing four functional variants and showing an excess of heterozygotes. Haplotype‐level tests failed to detect selection at these loci, but site‐specific tests detected signatures of positive selection within TLR3 and TLR15 . After characterizing variation (excluding TLR15 ) in 5–6 other Acrocephalus species, we found that TLR variation was positively correlated with population size across species and followed the pattern observed at neutral microsatellite loci. The depauperate TLR variation observed suggests that even at important immunity‐related loci, balancing selection may only attenuate the overriding effects of drift. However, in the SW, TLR15 appears to be an outlier and warrants further investigation. The low levels of TLR variation may be disadvantageous for the long‐term viability of the SW and conservation measures that maximize the retention of the variation should be considered. Abstract : In small populations, drift can result in a loss of genetic variation which can reduce adaptive evolutionary potential. However, under certain circumstances, balancing selection can counteract drift and maintain variation at functional loci. Identifying these loci can have important conservation implications and give insight into how different evolutionary forces interact in small populations. Here we investigate toll‐like receptor (TLR) genes that play a key role in vertebrate innate immune defence, and whether variation has been maintained at TLR loci in a bottlenecked population of the endangered Seychelles warbler. We find depauperate levels of variation that suggests drift is the dominating evolutionary force in this island population and this may well be disadvantageous for the long‐term viability of this species. Although the finding of variation of specific TLR loci, in spite of the recent bottleneck event, does warrant further study.